Portmanteau Constructions, Phrase Structure, and Linearization - Chan, Brian Hok-Shing (Frontiers in Psychology, 2015)
In bilingual code-switching which involves language-pairs with contrasting head-complement orders (i.e., head-initial vs. head-final), a head may be lexicalized from both languages with its complement sandwiched in the middle. These so-called “portmanteau” sentences (Nishimura, 1985, 1986; Sankoff et al., 1990, etc.) have been attested for decades, but they had never received a systematic, formal analysis in terms of current syntactic theory before a few recent attempts (Hicks, 2010, 2012). Notwithstanding this lack of attention, these structures are in fact highly relevant to theories of linearization and phrase structure. More specifically, they challenge binary-branching (Kayne, 1994, 2004, 2005) as well as the Antisymmetry hypothesis (ibid.). Not explained by current grammatical models of code-switching, including the Equivalence Constraint (Poplack, 1980), the Matrix Language Frame Model (Myers-Scotton, 1993, 2002, etc.), and the Bilingual Speech Model (Muysken, 2000, 2013), the portmanteau construction indeed looks uncommon or abnormal, defying any systematic account. However, the recurrence of these structures in various datasets and constraints on them do call for an explanation. This paper suggests an account which lies with syntax and also with the psycholinguistics of bilingualism. Assuming that linearization is a process at the Sensori-Motor (SM) interface (Chomsky, 2005, 2013), this paper sees that word order is not fixed in a syntactic tree but it is set in the production process, and much information of word order rests in the processor, for instance, outputting a head before its complement (i.e., head-initial word order) or the reverse (i.e., head-final word order). As for the portmanteau construction, it is the output of bilingual speakers co-activating two sets of head-complement orders which summon the phonetic forms of the same word in both languages. Under this proposal, the underlying structure of a portmanteau construction is as simple as an XP in which a head X merges with its complement YP and projects an XP (i.e., X YP → [XP X YP]).